Sistem Pendukung Keputusan Penilaian Kinerja Guru Dengan Metode Saw Pada Man 2 Tebo - Nurrahman, Nurrahman; Sarjono, Sarjono (Jurnal Manajemen Sistem Informasi, 2022)
MAN 2 Tebo is a high school under the auspices of the Ministry of Religion which is engaged in the field of Religion and Education. The development of a madrasa is determined by the number of students who register at the madrasa, of course with this increase it requires teachers who are competent and perform well in teaching. To improve good performance, of course, through teacher performance assessment, it is a very important thing in an educational institution. In this case, the process of assessing teacher performance is only limited to an assessment system for periodic salary and rank increases and there is no appreciation in terms of teacher performance appraisal. This is what causes the teacher to be a little unmotivated in performance. Therefore, based on these conditions, a teacher performance appraisal decision support system is needed that helps the head of madrasah in assessing teacher performance based on existing criteria. So the final result of this research is the design of a teacher performance appraisal decision support system with the SAW method which aims to facilitate decision making in determining teacher performance accurately and consistently.